Ceftriaxone Treatment for Neuronal Deficits: A Histological and MEMRI Study in a Rat Model of Dementia with Lewy Bodies. (1st August 2018) - Ho, Ying-Jui; Weng, Jun-Cheng; Lin, Chih-Li; Shen, Mei-Shiuan; Li, Hsin-Hua; Liao, Wen-Chieh; Tsai, Nu-Man; Hung, Ching-Sui; Lai, Te-Jen; Lee, I-Yen
Abstract : Dementia with Lewy bodies (DLB) is characterized by neuronal deficits and α -synuclein inclusions in the brain. Ceftriaxone (CEF), a β -lactam antibiotic, has been suggested as a therapeutic agent in several neurodegenerative disorders for its abilities to counteract glutamate-mediated toxicity and to block α -synuclein polymerization. By using manganese-enhanced magnetic resonance imaging (MEMRI) and immunohistochemistry, we measured the effects of CEF on neuronal activity and α -synuclein accumulation in the brain in a DLB rat model. The data showed that CEF corrected neuronal density and activity in the hippocampal CA1 area, suppressed hyperactivity in the subthalamic nucleus, and reduced α -synuclein accumulation, indicating that CEF is a potential agent in the treatment of DLB.